2016
DOI: 10.19030/jabr.v32i4.9725
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Corporate Governance On The Association Between Book-Tax Differences And Audit Quality: Evidence From Korea

Abstract: We investigate whether auditors input additional audit hours according to the sizes of book-tax differences (hereinafter BTD) and request additional audit fees for additional audit hours. In addition, the interaction effects of corporate governance on the relationships between BTD and audit hours/audit fees are examined using the total corporate governance (TCG) scores, data from the Korea Corporate Governance Service (KCGS). We predict that since auditors have the incentive and ability to consider BTD, audit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 30 publications
(34 reference statements)
0
13
1
3
Order By: Relevance
“…In this context, these results suggest that firms with better governance make more efforts for financial reporting in order to maintain their reliability in the market (Choi & Yang, ; Park et al, ). However, the finding of current study does not support the previous research of Oh et al (), who found in the Korean context that corporate governance effectiveness has a positive and significant effect on the relationship between BTDs and audit fees.…”
Section: Resultscontrasting
confidence: 99%
“…In this context, these results suggest that firms with better governance make more efforts for financial reporting in order to maintain their reliability in the market (Choi & Yang, ; Park et al, ). However, the finding of current study does not support the previous research of Oh et al (), who found in the Korean context that corporate governance effectiveness has a positive and significant effect on the relationship between BTDs and audit fees.…”
Section: Resultscontrasting
confidence: 99%
“…Research on the effect of BTD on time and cost of an audit has been done by [3]. The purpose of the study is to verify whether the auditor actually uses this information at the stage of the audit procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In his research, [3] also used corporate governance as a moderating variable. The reason why he used governance as a moderating variable is because of the positive and negative relationships (mixed results) between the effects of corporate governance on time-related and audit fees [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations